2016
DOI: 10.1016/j.aller.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Primary eosinophilic gastrointestinal disorders in children who have received food oral immunotherapy

Abstract: We report the highest prevalence of PEGDs in children subjected to OIT, and the first cases of eosinophilic gastroenteritis following food OIT. The monitoring of new digestive signs and symptoms after OIT is crucial for the diagnosis of these disorders, and prolonged follow-up is required. The management of such patients and the need or not to eliminate the food should be assessed on an individualised basis, according to the severity of the condition, its evolution and response to different treatment alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 26 publications
1
33
2
6
Order By: Relevance
“…Both Escudero et al and Burcks reported similar data, with fewer reactions and no severe reactions in the maintenance phase; nevertheless, Vazquez‐Ortiz et al observed the same frequency of reactions during the induction and maintenance phases with the same maintenance dose, but they require epinephrine treatment only during induction phase. Finally, unlike other studies, we did not observe development of esophagitis throughout the assay, despite the prolonged period of immunotherapy with high doses of the allergen, but esophagitis symptoms were an exclusion criteria in our study and other studies reporting these findings did not evaluate these symptoms at the start of the OIT.…”
Section: Discussionmentioning
confidence: 99%
“…Both Escudero et al and Burcks reported similar data, with fewer reactions and no severe reactions in the maintenance phase; nevertheless, Vazquez‐Ortiz et al observed the same frequency of reactions during the induction and maintenance phases with the same maintenance dose, but they require epinephrine treatment only during induction phase. Finally, unlike other studies, we did not observe development of esophagitis throughout the assay, despite the prolonged period of immunotherapy with high doses of the allergen, but esophagitis symptoms were an exclusion criteria in our study and other studies reporting these findings did not evaluate these symptoms at the start of the OIT.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, those with IgE‐mediated food allergy had significantly more dysphagia, poor appetite, cough and gagging at presentation than children without IgE‐mediated food allergy and heartburn was a much more common feature if IgE allergy was not present . There is also emerging evidence that in a small cohort of children who have undergone oral immunotherapy (OIT) for IgE‐mediated food allergies or grass pollen allergies, that they develop EGID as a side effect of the OIT …”
Section: Overlap Between Non‐ige‐mediated and Ige‐mediated Allergies mentioning
confidence: 99%
“…Blood tests showed a remarkable increase in peripheral blood eosinophil count, and endoscopic biopsy of the upper gastrointestinal tract revealed diffuse eosinophilic infiltration from the esophagus to the duodenum, confirming the diagnosis of EG with concurrent involvement of the esophagus [76] . A recent article has also reported 2 cases of EG following milk OIT [59] .…”
Section: Oit and Eg And Eosinophilic Colitismentioning
confidence: 99%
“…EC involves the large intestine alone [75] . Although there have been multiple case reports of EoE during or following OIT, little has been reported of EG, and as far as we know, no reports of EC during or following OIT exist [59,69,76] .…”
Section: Oit and Eg And Eosinophilic Colitismentioning
confidence: 99%
See 1 more Smart Citation